Modelling of seismic actions in earth retaining walls and comparison with shaker table experiment. Issue 150 (November 2021) - Tiwari, Rohit; Lam, Nelson
Abstract: This paper is concerned with the response behaviour of a retaining wall in seismic conditions from a two-dimensional perspective. The backfill was levelled behind the wall for some distance. Both the wall and the backfill were found on a stiff elastic medium. The manner in which the backfill affected the response behaviour of the wall when subject to base excitations was of interest. The wall was idealised into a linear elastic element which responded mainly in flexural actions. The novelty of the paper is in the use of shaker table testing of a scaled down model of the retaining wall and backfill to validate the accuracies of results from numerical simulations. The comparison is mainly based on displacement time - histories at the top of the wall. The alignment with displacement-based approach for the seismic assessment of structures is distinguished from many other investigations which typically put the focus on the behaviour of the backfill pressure. Laboratory testings of backfill materials including triaxial tests have been conducted to determine the value of parameters for characterising the hysteresis properties of the backfill. Calibration of backfill material model has also been shown to simulate the pre yield, post yield and damping behaviour of backfill. The ultimate objective of the paper is to present a viable means of achieving realistic and accurate modelling of the seismic response behaviour of a retaining wall and to provide data for benchmarking simplified (macro) numerical models to be developed in the future for supporting seismic design and assessment. Highlights: Shaking table experiment on scaled down retaining wall model. Characterization of backfill material based on detailed geotechnical testings. Constitutive modelling of backfill material. Finite element modelling of seismic actions on retaining walls. Evaluation of the capability of finite element modelling approach.